The impact of malaria-induced neutrophil subset shift and a link to Burkitt lymphoma - Sharon Akinyi Okoth; Ronald K. Tonui; Titus K. Maina; Eddy Agwati; Cliff I. Oduor; Zachary Racenet; Viriato M’Bana; Festus M. Njuguna; Kibet K. Keitany; Daniel Chepsiror; Cyrus Ayieko; Ann M. Moormann; et al. (PLoS ONE, 2026)
Burkitt lymphoma (BL) is an aggressive B-cell lymphoma that remains a leading cause of childhood cancer mortality in sub-Saharan Africa. Although the epidemiological link between Plasmodium falciparum (Pf) malaria and BL has been established, our understanding of the underlying immunological mechanisms conducive to tumorigenesis is incomplete. To address a noted gap in our knowledge of the immune landscape, we conducted a prospective study to profile neutrophil subsets from children with different exposure histories to Pf -malaria and children diagnosed with BL from Western Kenya, along with healthy malaria low-exposed Kenyan adults. Using multiparameter flow cytometry, we characterized neutrophils by expression of CD15, CD16, CD10, CD11b, CD182, CD184, and CD62L and found that malaria-exposed children exhibited increased frequencies of aged neutrophil subsets, accompanied by a reduction in the mature active subset frequencies compared to malaria low-exposed children. Notably, a positive correlation (rs = 0.7; p < 0.0001) was observed in immature neutrophils between malaria-exposed healthy and BL children, revealing a possible similar expansion of this subset in both groups. These findings suggest a malaria-associated expansion of the immature neutrophil subset. While functional assays were not performed in this study, previous reports indicate that immature neutrophils can exhibit tumor-promoting functions. Therefore, the observed shift in neutrophil profiles may reflect phenotypic changes associated with malaria exposure that could contribute to a permissive environment for BL.